2016
DOI: 10.3389/fmars.2016.00247
|View full text |Cite|
|
Sign up to set email alerts
|

Long-term Shifts in Coral Communities On Shallow to Deep Reef Slopes of Curaçao and Bonaire: Are There Any Winners?

Abstract: Tropical coral reefs are among the most biologically diverse and economically important ecosystems on earth. Nevertheless, we found dramatic changes in coral communities on the reef slopes of Curaçao and Bonaire since 1973. Cover and abundance declined for virtually all coral species. The data show a shift from communities dominated by framework building species (e.g., Orbicella spp.) to communities consisting of small opportunistic, phenotypically plastic, species, including few remaining structural colonies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 65 publications
2
66
1
3
Order By: Relevance
“…& Didier M. de Bakker didier.debakker@wur.nl; didierdebakker@gmail.com triggered shifts in benthic species composition, competition, productivity and biodiversity (Hughes 1994;Jackson et al 2014;De Bakker et al 2016a). The Caribbean region and Gulf of Mexico have been particularly affected with an estimated decrease in scleractinian coral cover up to 80% on many reefs.…”
Section: Communicated By Ecology Editor Dr Alastair Harbornementioning
confidence: 99%
“…& Didier M. de Bakker didier.debakker@wur.nl; didierdebakker@gmail.com triggered shifts in benthic species composition, competition, productivity and biodiversity (Hughes 1994;Jackson et al 2014;De Bakker et al 2016a). The Caribbean region and Gulf of Mexico have been particularly affected with an estimated decrease in scleractinian coral cover up to 80% on many reefs.…”
Section: Communicated By Ecology Editor Dr Alastair Harbornementioning
confidence: 99%
“…De bodembedekking door levend koraal is de afgelopen 40 jaar gemiddeld met meer dan 50% afgenomen (Bak et al 2005a, de Bakker et al 2016, de Bakker et al 2017. Bij een verdere achteruitgang dreigen belangrijke ecosysteemdiensten zoals toerisme, visserij en kustbescherming de komende jaren sterk achteruit te gaan.…”
Section: Aspect Zeegrasvelden 2017unclassified
“…Lange-termijn data zijn alleen bekend van Bonaire en Curaçao, (Bak et al, 2005b;de Bakker et al, 2016;de Bakker et al, 2017 Bakker et al, 2016;de Bakker et al, 2017). Andere data worden besproken in Jackson et al (2014), maar de conclusies, namelijk een afname van bijna 50% van de oorspronkelijke bedekking gedurende de laatste 25-40 jaar, zijn dezelfde als hier (Fig.…”
Section: Trendsunclassified
See 1 more Smart Citation
“…For example, van Duyl (1985) mapped out bottom types and benthic community structure around the leeward perimeter of the island from the shoreline to a depth of ∼10 m. There have been limited observations of reefs in Bonaire at greater depths and almost no work has been done to date at depths where Mesophotic Coral Ecosystems (referred to in the research literature as MCEs) exist. A recent study by De Bakker et al (2016) reported pressures and declines in coral assemblages even in depths of 30-40 m off Bonaire and Curaçao thus emphasizing the need to locate and characterize coral reef assemblages in mesophotic depths. MCEs in Bonaire have been shown to extend from 30 to 150 m water (De Meyer and MacRae, 2006;Keller, 2011).…”
Section: Introductionmentioning
confidence: 99%